2019
DOI: 10.5152/eurasianjmed.2018.17381
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Clinicopathological Factors of the Tumor with Preoperative TSH Level in Papillary Thyroid Cancers

Abstract: Aims and Scope Eurasian Journal of Medicine (Eurasian J Med) is an international, scientific, open access periodical published by independent, unbiased, and tripleblinded peer-review principles. The journal is the official publication of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The number of studies evaluating the relationship between clinicopathological features and TSH is limited in the literature. TSH level was found to be an independent predictive factor for extrathyroidal spread and central metastasis in PTC in one study, [9] and an independent predictive factor for extrathyroidal spread and lateral metastasis in DTC in another study. [13] Other studies have shown that the rate of central metastasis is high, especially in the presence of pathological features such as extrathyroidal spread, multifocality, lymphovascular invasion, and capsular invasion.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The number of studies evaluating the relationship between clinicopathological features and TSH is limited in the literature. TSH level was found to be an independent predictive factor for extrathyroidal spread and central metastasis in PTC in one study, [9] and an independent predictive factor for extrathyroidal spread and lateral metastasis in DTC in another study. [13] Other studies have shown that the rate of central metastasis is high, especially in the presence of pathological features such as extrathyroidal spread, multifocality, lymphovascular invasion, and capsular invasion.…”
Section: Discussionmentioning
confidence: 91%
“…Studies on this subject are limited. [9,10] The data to be obtained in this regard may contribute to the determination of the surgical extent of the patients, the post-operative risk classification, and the planning of the treatment.…”
mentioning
confidence: 99%
“…New techniques also bring with them approach speci c complications [15,16] . For instance, the increased risk of infection from transforming a clean procedure to a clean contaminated operation were key concerns following the introduction of conventional transoral endoscopic thyroid surgery [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Thyrotropin is a recognized factor of development (9). Several studies have shown an increased risk of thyroid cancer in people with nodular thyroid disease and the connection between high preoperative TSHs (10). Moreover, a recent meta-analysis indicated the increased risk of PTC in relation to a greater level of serum TSH (11).…”
Section: Introductionmentioning
confidence: 99%